INTERPRETATION OF THE HERO IN OIBEK'S FAIRY TALES FOR CHILDREN (Scientific journal of the Fergana State University, 2024)
The article examines the stories of Musa Tashmuhammad Aybek written for children. "Sister Gulnor", "Fanorchi Ota", "Musicha", "Bullet for the Game", as well as "Poor Children", "Bloody Fingers", dedicated to the life of foreign children, were published for the first time in the twelfth volume of his "Collection of Perfect Works". issues of artistic style and skill are researched through the analysis of stories.